The book of illusions - Auster, Paul, 1947- (New York, NY : Picador, 2003)
Six months after losing his wife and two young sons in an airplane crash, Vermont proffesor David Zimmer spends his waking hours mired in a blur of alcoholic grief and self-pity. Then his life changes when watching television one night.
Keywords: American fiction